2019
DOI: 10.1186/s12885-019-5883-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of clonal communication and heterogeneity in breast cancer

Abstract: Background Cancer is a rapidly evolving, multifactorial disease that accumulates numerous genetic and epigenetic alterations. This results in molecular and phenotypic heterogeneity within the tumor, the complexity of which is further amplified through specific interactions between cancer cells. We aimed to dissect the molecular mechanisms underlying the cooperation between different clones. Methods We produced clonal cell lines derived from the MDA-MB-231 breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 67 publications
(80 reference statements)
0
34
0
1
Order By: Relevance
“…The concept of clonal cooperation is based on a single clone being unable to acquire all the necessary properties to be an invasive tumor, such that various clones must act synergistically and complementarily to acquire the characteristics described by Hanahan and Weinberg [49] and the proposed biochemical changes in 10 or more cellular biochemical pathways. This cell cooperation can be observed in cell clusters in metastatic development: clusters of circulating tumor cells (CTCs) are associated with higher number of metastases than single circulating cells in models of breast cancer, pancreatic cancer, and melanoma [50,51,[102][103][104][105][106]. Moreover, our group made an effort to generate MDA-MB-231 breast cancer cell lines single clones and demonstrated that the clonal cooperation confers aggressiveness and tumor progression [106].…”
Section: Proteomic Heterogeneity: Going Beyond the Genomementioning
confidence: 91%
“…The concept of clonal cooperation is based on a single clone being unable to acquire all the necessary properties to be an invasive tumor, such that various clones must act synergistically and complementarily to acquire the characteristics described by Hanahan and Weinberg [49] and the proposed biochemical changes in 10 or more cellular biochemical pathways. This cell cooperation can be observed in cell clusters in metastatic development: clusters of circulating tumor cells (CTCs) are associated with higher number of metastases than single circulating cells in models of breast cancer, pancreatic cancer, and melanoma [50,51,[102][103][104][105][106]. Moreover, our group made an effort to generate MDA-MB-231 breast cancer cell lines single clones and demonstrated that the clonal cooperation confers aggressiveness and tumor progression [106].…”
Section: Proteomic Heterogeneity: Going Beyond the Genomementioning
confidence: 91%
“…c The assignment of unique fingerprints to targeted progenitors enabled sibling cells to be identified and their relationships due to the generation of a specific and stable barcode in the cells. d However, the new tools generated to decipher genomic information in an entire organism enable a wealth of important information to be drawn that helps to reconstruct the lineage trees of cells and their sibling connections described in the progression of squamous carcinomas [119], sarcomas [120] and breast cancers [121]. In the CNS, glioblastoma cells engage in clonal communication based on cell-cell contact [122].…”
Section: Insights Into the Lineage Tracing Of Neural Cells From Clonamentioning
confidence: 99%
“…For SVs, no overlap of somatic SVs and genes were found between amplified bulk cancer and spike-in samples. One of the possible explanations for the discrepancy in the overlap of somatic alterations may be due to cellular heterogeneity within the same type of cancer cells [30,31]. Despite the importance of cellular heterogeneity, another reason may be due to the high variability of cell size.…”
Section: Optimization Of Wes In Spiked and Unspiked Breast Cancer Cellsmentioning
confidence: 99%